Conductive filler and preparation method thereof, conductive adhesive, and application thereof
By using three-layer conductive filler, the filler network structure of the conductive glue is optimized, and the problems of low flow rate and blockage of conductive glue during the dispensing process are solved, and high shielding performance and excellent dispensing process performance are achieved.
Patent Information
- Application Number
- CN202310344440.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-04-03
AI Technical Summary
The prior art is difficult to take into account high shielding performance and excellent dispensing process performance in conductive adhesives, resulting in problems such as low flow rates, blockage, oil seepage and bubbles.
The conductive filler with a three-layer structure is adopted, including conductive metal powder as the core layer, silicone resin as the intermediate layer and silica or polysilsesquioxane as the shell layer. By controlling the mass ratio and surface area ratio of each layer, the filler network structure is optimized to improve rheological performance.
It realizes high flow rate, low flow resistance, stability and high storage stability during the dispensing process, and has high shielding performance, solving the problems of low flow rate and blockage of conductive glue in the prior art.
Smart Images

Figure BDA0004161237710000081 
Figure BDA0004161237710000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive materials, and more specifically to a conductive filler and a preparation method thereof, a conductive adhesive and applications thereof. Background Art
[0002] With the rapid development of the communications industry, various electronic products are gradually moving towards lighter and thinner, which means that the shielding materials used in electronic products have to move towards lighter and thinner at the same time. That is, shielding rubber strips and rubber sheets will gradually shift to small-sized, fast-forming conductive adhesive (Form-In-Place, FIP) materials.
[0003] For FIP materials formed by dispensing process, poor FIP materials often have problems in the dispensing process such as low flow rate, blockage, oil seepage, bubbles, etc. How to prepare FIP materials with both high shielding functionality and excellent dispensing process performance has always been a technical difficulty restricting the development of FIP materials. Thixotropy is one of the important indicators of FIP materials. Thixotropy refers to the ability of materials to maintain aspect ratio. For example, the initial dispensing shape of high thixotropic FIP materials is 1.5 high and 1.0 wide. Over time, this product will not become shorter or wider.
[0004] In the prior art, the shielding performance of the product is ensured by adding a large amount of conductive powder. At the same time, in order to achieve a higher flow rate to ensure the product's dispensing processability, the purpose of high flow rate can only be achieved by adding a large amount of solvent, which causes bubbles and stratification during the dispensing process. This contradiction limits the application of FIP materials. It can be seen that the research content of the prior art is mostly limited to the single goal of shielding performance. The disadvantage of FIP materials is that they only achieve high shielding performance brought by high filling amount, and cannot achieve both high shielding performance and good dispensing processability. In particular, the use of two-component conductive FIP molding process has higher requirements for dispensing processability and greater technical difficulty. In short, the industry currently lacks FIP materials that have both high shielding and excellent dispensing process performance. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a conductive filler and a preparation method thereof, a conductive adhesive, and an application. The inventors have conducted in-depth research to achieve the above-mentioned purpose, and found that the conductive adhesive prepared using the conductive filler provided by the present invention has both high shielding performance and excellent dispensing process performance.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A conductive filler, comprising:
[0008] nuclear layer;
[0009] an intermediate layer disposed on the nuclear layer;
[0010] a shell layer disposed on the intermediate layer;
[0011] The core layer is conductive metal powder;
[0012] The middle layer is a silicone resin;
[0013] The shell layer is one or more of silicon dioxide, polysilsesquioxane, and MQ silicone resin;
[0014] The resistivity of the conductive filler is 0.001-0.01Ω·mm.
[0015] MQ silicone resin is composed of monofunctional chain segments (R3SiO 1 / 2 , i.e. M) and tetrafunctional chain (SiO 4 / 2 , that is, Q) composed of an organic / inorganic hybrid polysiloxane with a special structural ratio.
[0016] In the present invention, the resistivity of the conductive filler is 0.002-0.006Ω·mm, preferably 0.004Ω·mm;
[0017] The mass ratio of the intermediate layer to the core layer is (0.2-1):100, preferably 0.5:100; if the mass ratio of the intermediate layer to the core layer is less than 0.2:100, the core layer and the intermediate layer are not firm, resulting in an unstable three-layer structure of the conductive filler and a loss of the rheological control effect of high flow rate and high thixotropy;
[0018] The mass ratio of the shell layer, the middle layer and the core layer is (0.6-2.8):(0.2-1):100, preferably (1-2):(0.2-1):100, and more preferably 1.5:0.5:100; if the ratio of the shell layer is >2.8:(0.2-1):100, the conductivity of the conductive filler is damaged, thereby causing the shielding performance of the conductive adhesive product to be damaged; if the ratio of the shell layer is <0.6:(0.2-1):100, the shell layer is too small, resulting in an incomplete shell structure that impairs the rheological control effect.
[0019] The surface area ratio of the shell layer to the core layer is (1-20):1, preferably 3.6:1; if the surface area ratio of the shell layer to the core layer is too small, the three-layer structure of the conductive filler and the base glue interface will have too weak interaction, poor thixotropy and loss of high flow rate and high thixotropy; if the ratio is too large, the three-layer structure of the conductive filler and the base glue interface will have too strong interaction, the flow rate will be low and the rheological control effect of high flow rate and high thixotropy will be lost. The rheological control effect specifically refers to: under high flow rate conditions, the material can still have a good ability to maintain its aspect ratio; if the interaction between the filler and the base glue is too strong, the flow rate will be very low and there will be no rheological ability.
[0020] In the present invention, the conductive metal powder is one or more of nickel-coated graphite powder, silver-plated aluminum powder, silver-plated nickel powder, and nickel-plated aluminum powder;
[0021] The D50 of the conductive metal powder is 70-150 μm, preferably 100 μm;
[0022] The ratio of D90 to D10 of the conductive metal powder is (2-5):1, preferably (2-3):1; if the ratio of D90 to D10 is too large or too small, the filler network is uneven, resulting in unqualified shielding properties of the product; D50, D90, and D10 can be tested using a laser diffraction particle size analyzer, and the particle size distribution is calculated based on the volume distribution, which respectively represent the area lengths when the cumulative values are 50%, 90%, and 10% when the cumulative curve is obtained from the small particle size side of the particle size distribution.
[0023] The BET specific surface area of the conductive metal powder is 0.2-0.8 m 2 / g, preferably 0.5m 2 / g.
[0024] In one embodiment of the present invention, the conductive metal powder is nickel-coated graphite powder, D50 is 100 μm, D90 and D10 ratio is 2.7:1; the aspect ratio of the nickel-coated graphite powder is 1.5-3, preferably 2; the BET specific surface area of the nickel-coated graphite powder is 0.5 m 2 / g. The specific surface area was measured using a specific surface area analyzer using a static capacity method.
[0025] In the present invention, the silicone resin is polysiloxane;
[0026] The molecular weight of the silicone resin is 600-2000, preferably 800;
[0027] The organosilicon resin contains reactive functional groups;
[0028] The grafting density of the reactive functional group is 0.5-10 mmol / g, preferably 5 mmol / g; the grafting density of the reactive functional group can be calculated from the functional group content and the specific surface area;
[0029] The reactive functional group is vinyl and / or acyloxy, preferably vinyl.
[0030] In the present invention, the D50 of the shell layer is 10-500nm, preferably 50nm; if the shell layer powder D50 is <10nm, the viscosity is seriously increased, and if it is >500nm, the adhesion to the middle layer is not strong, resulting in an unstable three-layer structure of the conductive filler and loss of high flow rate and high thixotropy.
[0031] The BET specific surface area of the shell layer is 150-180 m 2 / g, preferably 120-180m 2 / g, more preferably 120m 2 / g; the specific surface area is measured by a specific surface area analyzer using a static capacity method;
[0032] The shell layer is preferably nano-scale spherical powder.
[0033] In the present invention, the D50 of the conductive filler is 80-160 μm, preferably 120 μm.
[0034] The present invention also provides a method for preparing the conductive filler, comprising:
[0035] (1) coating the conductive metal powder with an organic silicone resin to obtain a mixture; wherein the core layer of the mixture is the conductive metal powder and the outer layer is the organic silicone resin;
[0036] (2) The mixed material obtained in step (1) is coated with a raw material for preparing a shell layer to form a shell layer on the outside of the mixed material to obtain a conductive filler.
[0037] The preparation method of the mixture includes: mixing an organic silicone resin with an acid to obtain an organic silicone resin treating agent, and then coating a conductive metal powder with the organic silicone resin to obtain a mixture; the volume ratio of the organic silicone resin to the acid is 1:(0.01-0.1); preferably, the organic silicone resin is mixed with the acid and a solvent; the solvent is preferably one or more of water, ethanol, and propanol; in one embodiment of the present invention, the organic silicone resin treating agent is a mixture of polysiloxane, water, ethanol, and acetic acid in a volume ratio of 1:1:10:0.01.
[0038] The organic silicon resin of the present invention is hydrolyzed under acidic conditions to form -OH groups, and the hydroxyl groups and the conductive metal powder can form a stable coating through unconventional hydrogen bonding, and the shell material further forms a stable structure through the difference in specific surface area with the organic silicon resin and the action of hydrogen bonding.
[0039] The method for preparing the conductive filler preferably comprises:
[0040] 1) mixing an organosilicon resin, an acid and a solvent to obtain an organosilicon treatment agent;
[0041] 2) Mixing and coating the organosilicon treatment agent with the conductive metal powder to form a resin intermediate layer; the amount of the coating agent is 0.2% to 1% of the mass of the conductive metal powder; the shear rate during the mixed coating is 1 to 5 m / s, the spraying rate is 1 to 2 g / s, and the temperature is 100 to 200° C.; the mixed coating is preferably performed by uniformly spraying the organosilicon treatment agent on the powder surface; the amount of the coating agent is 1% of the mass of the conductive metal powder;
[0042] 3) The shell layer and the product of the previous step are coated again to form the outermost layer to form a conductive filler. The amount of the shell layer is 0.6% to 2.8% of the mass of the conductive metal powder, preferably 1.5%; the shear line speed of the coating is 1 to 2 m / s, and the coating temperature is 60 to 100°C.
[0043] The present invention also provides the above conductive adhesive, comprising the conductive filler, organic silicon polymer, crosslinking agent and catalyst; the electromagnetic shielding property of the conductive adhesive is ≥115dB (300MHz~10GHz).
[0044] In the present invention, the volume filling rate of the conductive filler in the conductive adhesive is ≥50%, preferably 85%;
[0045] The organosilicon polymer is vinyl silicone oil;
[0046] The catalyst is a platinum catalyst, and the platinum content is 10-20ppm of the vinyl silicone oil;
[0047] The cross-linking agent is hydrogen-containing silicone oil.
[0048] The conductive adhesive also includes a diluent; the diluent is a hydrocarbon diluent, and the amount used is 10-15wt% of the vinyl silicone oil.
[0049] The conductive adhesive of the present invention can be a single-component material or a two-component material. In one embodiment of the present invention, the conductive adhesive consists of a first component and a second component; the mass ratio of the first component to the second component is 1:1; the first component includes: vinyl silicone oil, platinum catalyst, white carbon black reinforcing agent, conductive filler, hydrocarbon diluent; the second component includes: vinyl silicone oil, hydrogenated silicone oil, white carbon black reinforcing agent and conductive filler.
[0050] The present invention has no special limitation on the preparation method of the conductive adhesive, which preferably includes: stirring and homogenizing the conductive filler, vinyl silicone oil, a crosslinking agent and a catalyst, and curing and molding to obtain the conductive adhesive.
[0051] The invention also provides application of the conductive adhesive in a dispensing process.
[0052] The dispensing process is a Form in Place (FIP) process.
[0053] The conductive adhesive of the present invention can be used in the interface gap between two contact materials on electronic components to play the role of electromagnetic shielding, and is particularly suitable for application scenarios with large gaps > 1 mm and a dispensing aspect ratio < 0.9.
[0054] The conductive adhesive of the present invention can be cured and formed after being heated at 150° C. for 30 minutes.
[0055] The problem that those skilled in the art have not discovered is that for conductive adhesive products with high filler loading, various dispensing process problems, such as low flow rate, blockage, oil seepage, bubbles, etc., are greatly affected by the conductive filler network structure under high filling. In order to achieve good dispensing processability of conductive adhesive, including high thixotropy, extrusion fluidity, high flow rate stability and high storage stability, the inventors conducted in-depth research, specifically starting from the perspective of the influence of the conductive filler network interface structure of FIP material on the rheological properties of the material, and innovatively designed the filler network interface structure. The specific relationship between the structure and performance is as follows:
[0056] First, the conductive filler powder is controlled to have a layer of organic silicone resin with functional groups on its surface, ensuring that different conductive particles in the filler network have appropriate interfacial forces and reactive functional groups, so that the sum of the interfacial resistances in the entire particle system during extrusion of the conductive adhesive is minimized, and at the same time, the particle network is stabilized in a static state, thereby effectively avoiding the low flow rate and blockage of the conductive adhesive;
[0057] Second, the conductive filler powder of the present invention has a layer of powder on its surface, preferably nano-scale spherical powder, which can play a role in absorbing the base glue, so that all particles and the base glue move simultaneously when the material is extruded and flows, and at the same time play a uniform role, making the particle network dynamically stable, thereby effectively avoiding oil seepage and bubble problems;
[0058] The results show that this type of filler network structure can not only ensure a high filling amount to improve shielding performance, but also ensure that the material has low flow resistance under the extrusion flow state during the dispensing process, thereby improving the extrusion fluidity of dispensing; it has high dynamic network structure stability, thereby improving the extrusion flow stability; it has high static network structure stability, thereby improving storage stability. Finally, material preparation is achieved through precise filler control technology.
[0059] It is confirmed by the embodiments of the present invention that in the investigation of dispensing processability, the initial dispensing flow rate of the two-component conductive adhesive of the present invention is >20g / min, the flow rate decays <4% after continuous dispensing for 4h, the extrusion speed decays <5% after refrigerated storage for 7 days, and the extrusion speed decays <4% after mixing of the unmixed two-component material after the shelf life of 6 months; in the investigation of the molding process, the conductive adhesive is placed on the surface of the lower interface material in a triangular shape with an aspect ratio of 0.7, and can be cured and molded after heating at 150°C for 30min; in the investigation of the electromagnetic shielding effect, the shielding effectiveness test result of the cured FIP is ≥115dB (300MHz~10GHz), which shows that the conductive adhesive of the present invention has both high shielding performance and excellent dispensing process performance, and the dispensing process performance specifically includes high thixotropy, extrusion fluidity, high flow rate stability and high storage stability. DETAILED DESCRIPTION
[0060] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0061] In order to further illustrate the present invention, the following examples are provided for detailed description. The raw materials used in the following examples of the present invention are all commercially available commodities.
[0062] The conductive metal powder used in the embodiment of the present invention is nickel-coated graphite Ni / C powder, the mass content of nickel is 60%, the ratio of D90 to D10 of the powder is 2.7, the D50 is 100 μm, the powder is flake-shaped, the aspect ratio is 2, and the BET specific surface area is 0.5 m 2 / g; the silicone resin is a polysiloxane with a C=C side chain, a molecular weight of 800, a vinyl functional group, and an effective grafting density of 5mmol / g; the spherical nano-silica powder has a D50 particle size of 50nm and a BET specific surface area of 120m 2 / g. The specific surface area was measured using a specific surface area analyzer using a static capacity method.
[0063] Example 1 Conductive filler
[0064] The preparation method of the conductive filler comprises:
[0065] 1) polysiloxane, water, ethanol and acetic acid are mixed in a volume ratio of 1:1:10, and then acetic acid is added in an amount of 1 / 100 of the volume of polysiloxane to obtain an organosilicon treatment agent, which is used as a coating agent for standby use;
[0066] 2) Add Ni / C powder to the mixer, start the powder mixer, maintain the shear rate of 2m / s, the reaction temperature of 100°C, and evenly spray the coating agent on the powder surface. The amount of the coating agent is 1% of the mass of the core layer, and the spraying rate is 1g / s. In the equipment, the organosilicon treatment agent is coated on the surface of the Ni / C powder to obtain an intermediate product. In the intermediate product, the mass ratio of the resin layer to the Ni / C powder is 5:1000;
[0067] 3) Add spherical nano-silicon dioxide powder and the intermediate product obtained in the previous step into a high-speed mixer, wherein the amount of spherical nano-silicon dioxide powder is 1.5% of the mass of the core layer, the shear line speed of the mixer is controlled to be 2 m / s, the coating temperature is 60° C. The raw materials are uniformly mixed under the above conditions to form a final conductive filler, wherein the D50 of the conductive filler is 120 μm, the resistivity is 0.004 Ω·mm, the core layer is nickel-coated graphite Ni / C powder, the intermediate layer is polysiloxane, and the shell layer is spherical nano-silicon dioxide.
[0068] Example 2 FIP material
[0069] 1) Component information of FIP:
[0070] FIP consists of component A and component B, and the mass ratio of component A to component B is 1:1;
[0071] Component A includes: vinyl silicone oil (base material), platinum catalyst, white carbon black reinforcing agent, conductive filler, hydrocarbon diluent, wherein the platinum content is 10ppm of the mass of the vinyl silicone oil, the mass of the white carbon black reinforcing agent is 1% of the mass of the vinyl silicone oil, and the mass of the hydrocarbon diluent is 10% of the mass of the vinyl silicone oil. The volume filling rate of the conductive filler in component A is 85%;
[0072] Component B includes: a mixture of vinyl silicone oil and hydrogen-containing silicone oil (base material), a white carbon black reinforcement and a conductive filler, wherein the molar ratio of the vinyl group of the vinyl silicone oil to the silicon hydrogen group of the hydrogen-containing silicone oil is 1:2, the mass of the white carbon black reinforcement is 1% of the mass of the vinyl silicone oil, and the mass of the hydrocarbon diluent is 10% of the mass of the vinyl silicone oil; the volume filling rate of the conductive filler in component B is 85%; the molar ratio of the vinyl group in the total vinyl silicone oil of group AB to the silicon hydrogen group of the hydrogen-containing silicone oil is 1:1.
[0073] 2) Preparation method of FIP:
[0074] Conductive filler powder and base material are kneaded and homogenized in stages, and the ratio of the two is controlled in the stage-by-stage process;
[0075] The vinyl silicone oil, platinum catalyst, white carbon black reinforcing agent and hydrocarbon diluent of component A are stirred and homogenized at a stirring speed and linear velocity of 40m / s to obtain the base rubber of component A; the vinyl silicone oil, white carbon black reinforcing agent and hydrogen-containing silicone oil raw materials of component B are stirred and homogenized at a stirring speed and linear velocity of 40m / s to obtain the base rubber of component B; the conductive filler is added to the base rubber of component A and the base rubber of component B in 5 stages for kneading and homogenization, and the vacuum degree is -0.99kPa; FIP is obtained, and finally potted into the A and B rubber hoses.
[0076] 3) Application process and effect:
[0077] 3.1) Dispensing processability inspection: After A and B are fully mixed, they are poured into a 300cc hose. At 90psi, the dispensing speed is >20g / min. After continuous dispensing for 4 hours, the flow rate decays by <4%. After refrigerated storage for 7 days, the extrusion speed decays by 5%. Within the validity period of 6 months, the extrusion speed of AB unmixed materials decays by 5% after mixing.
[0078] 3.2) Molding process: The FIP is placed on the surface of the lower interface material through a dispensing process. The shape is triangular with an aspect ratio of 2.5 / 3.5. It is heated at 150°C for 30 minutes and then cured.
[0079] 3.3) Shielding effect investigation: The shielding effectiveness of the cured FIP was tested, and the result was: >115dB (300MHz~10GHz), see Table 1 and Table 2 for details.
[0080] Comparative Example 1
[0081] Changing the content of the silicone resin in the middle layer will affect the thixotropy and flow rate of the final material, and ultimately affect the dispensing processability of the product.
[0082] Comparative Example 2
[0083] Changing the amount of silicone powder added to the outer layer will affect the thixotropy and flow rate of the final material, and ultimately affect the dispensing processability of the product.
[0084] Table 1
[0085]
[0086] Table 2
[0087]
[0088] It can be seen from Table 1, Table 2 and the dispensing processability inspection that only by coating according to the specific parameters of the present invention can the FIP material be guaranteed to have excellent dispensing processability, including high thixotropy, extrusion fluidity, high flow rate stability and high storage stability, on the basis of high shielding performance brought by high filling amount.
[0089] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A conductive filler, characterized in that: include: nuclear layer; an intermediate layer disposed on the nuclear layer; a shell layer disposed on the intermediate layer; The core layer is conductive metal powder; The middle layer is a silicone resin; The shell layer is one or more of silicon dioxide, polysilsesquioxane, and MQ silicone resin; The resistivity of the conductive filler is 0.001-0.01Ω·mm; The mass ratio of the shell layer, the intermediate layer and the core layer is (0.6-2.8):(0.2-1):100; The ratio of D90 to D10 of the conductive metal powder is (2-5):1; The D50 of the shell is 10-500nm; The organosilicon resin contains reactive functional groups; The reactive functional group is vinyl and / or acyloxy.
2. The conductive filler according to claim 1, characterized in that: The conductive metal powder is one or more of nickel-coated graphite powder, silver-plated aluminum powder, silver-plated nickel powder, and nickel-plated aluminum powder; The organic silicone resin is polysiloxane.
3. The conductive filler according to claim 1, characterized in that: The D50 of the conductive metal powder is 70-150 μm.
4. The method for preparing a conductive filler according to any one of claims 1 to 3, characterized in that: include: (1) coating the conductive metal powder with an organic silicone resin to obtain a mixture; wherein the core layer of the mixture is the conductive metal powder and the outer layer is the organic silicone resin; (2) The mixed material obtained in step (1) is coated with a raw material for preparing a shell layer to form a shell layer on the outside of the mixed material to obtain a conductive filler.
5. The method for preparing the conductive filler according to claim 4, characterized in that: The preparation method of the mixture comprises: mixing an organic silicon resin with an acid to obtain an organic silicon resin treating agent, and then coating the conductive metal powder with the organic silicon resin to obtain the mixture.
6. Conductive adhesive, characterized in that: Comprising the conductive filler according to any one of claims 1 to 3, an organosilicon polymer, a crosslinking agent and a catalyst; The electromagnetic shielding property of conductive adhesive is ≥115dB.
7. The conductive adhesive according to claim 6, characterized in that: The volume filling rate of the conductive filler in the conductive adhesive is ≥50%.
8. The conductive adhesive according to claim 6, characterized in that: The organosilicon polymer is vinyl silicone oil; The catalyst is a platinum catalyst; The cross-linking agent is hydrogen-containing silicone oil.
9. Use of the conductive adhesive as described in any one of claims 6 to 8 in a dispensing process.
Citation Information
Patent Citations
Thermal interface material with low Young modulus and high thermal conductivity as well as preparation method and application thereof
CN112447634A
Electroconductive metal paste
CN1478285A
Cited By
Two-component nickel-coated aluminum room temperature curing conductive adhesive as well as preparation method and application thereof
CN122790605A